Biological Sulfide Oxidation and Its Impact on Cell Biomass Synthesis by Mesophilic Bacterium Bacillus Cereus (ATCC 14579) - Mani Malam, Ahmad; A. M., Azoddien; Zahari, Mohamad; M. N., Seman; M. S., Jami (Universiti Malaysia Pahang, 2017)
Inhibitory effects of hydrogen sulfide could either be due to toxicity to living tissue or precipitation of sulfide salts which inhibit its utilization for cell growth. Growth, is undoubtedly affected by certain conditions, among which are nutrient types and availability, as well as the operational parameters of the fermenting medium. In this study, Bacillus cereus (ATCC 14579) was tested for potential sulfide biodegradation in a suspended growth medium of orbital shake flasks using a single milieu composition under defined operational parameters. Growth and sulfide oxidation efficiency were measured pectrophotometrically under optimum physical conditions of pH, temperature, acclimatization time and agitation. Sulfide reduction was overwhelmingly recorded at three different sulfide loading rates of 200 ppm S2- L-1 d-1, 300 ppm S2- L-1 d-1 and 500 ppm S2- L-1 d-1 with corresponding appreciable cell growth measured at OD600 nm. Results indicated that it was possible to realise sulfide removal efficiency of 95% to 99% using this strain in an orbital shake flask within 24 hrs, as well as 65% to 78% within the first 6 hrs of inoculation. Overall, sulfide was reduced by 95% in 200 ppm and 300 ppm, while 99% in 500 ppm, respectively. While, the corresponding exponential cell growth recorded was 3.91, 3.80 and 3.61 in 200 ppm, 300 ppm and 500 ppm, respectively. This also translate to cell biomass synthesis (cell dry weight) of 0.61 g/L, 0.58 g/L and 0.50 g/L in 200 ppm, 500 ppm and 300 ppm. Based on this finding, it was clear that this inoculum can utilize different sulfide concentration for growth and biosynthesis; thus can be employed to treat sulfide contaminated wastewater in a suspended growth form under simple nutrient composition and operational conditions.